PENGARUH KOORDINASI, KOMUNIKASI, DAN KOMPETENSI TERHADAP KINERJA PEGAWAI SEKRETARIAT BADAN PENDIDIKAN DAN PELATIHAN KEUANGAN (BPPK) KEMENTERIAN KEUANGAN REPUBLIK INDONESIA - Dhifa Fitry Fadhiyah (2022)
The research was carried out with the aim of knowing and proving whether there was an influence on Coordination, Communication, and Competence on Employee Performance in non-echelon employees of the Secretariat of the Financial Education and Training Agency (BPPK) of the Ministry of Finance of the Republic of Indonesia, amounting to 68 people. The number of non-echelon employees is obtained by using the Probability Sampling technique with the Simple Random Sampling technique by means of a lottery. the test equipment in processing the research data was carried out using the SmartPLS 3.0 application using the Partial Test (T test) and Simultaneous Test (F test). The results obtained from this study are (1) there is a positive and significant effect of Coordination on the Performance of Secretariat Employees of the Financial Education and Training Agency of the Republic of Indonesia. (2) there is a positive and significant effect of Communication on the Performance of Secretariat Employees of the Financial Education and Training Agency of the Republic of Indonesia. (3) there is a positive and significant effect of Competence on the Performance of the Secretariat Employees of the Financial Education and Training Agency of the Republic of Indonesia (4) there is a simultaneous influence on the performance of the Secretariat Employees of the Financial Education and Training Agency of the Republic of Indonesia. Keywords : Human Resources, Employee Performance, Coordination, Communication, and Competence